Penerapan Model Pembelajaran Hannafin&Peck Dalam Materi Trigonometri Sudut Istimewa Melalui Alat Peraga Trisuis Kelas X Di SMK Yadika 8 Jatimuliya - Tasya Maria Agustin Marpaung; Nasywa Mahesa; Adrianus Raibon Piran; Mualim Gorang; Ibu Leny Hartati (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this article is to find out about learning planning using the Hannafi&Peck model. This model uses product-oriented learning media design development. This research is also used to produce a product that wants to be developed through a trisuis teaching aid in special angle trigonometry material in Class X of SMK Yadika 8 Jatimuliya. These teaching aids can make it easier for students to remember the special angles of trigonometry more easily. Because in general children understand material more quickly if they use learning videos or teaching aids. Thus, this teaching aid aims to see whether it is easier for students to understand special angle trigonometry material.